(untitled) (Eurasian Medical Research Periodical, 2025)
The concept of “diastolic dysfunction” is based on both structural and functional remodeling of cardiomyocytes and the interstitial matrix, leading to increased myocardial stiffness [2,4]. Unlike systole, during which Ca²⁺ ions are actively released from the sarcoplasmic reticulum into the cytosol, myocardial relaxation is an energy-dependent process associated with the active transport of Ca²⁺ ions back into the sarcoplasmic reticulum against a concentration gradient [10]. This mechanism explains why disturbances in myocardial relaxation occur earlier than systolic dysfunction, particularly under conditions of myocardial ischemia in ischemic heart disease (IHD) [3,6,9]. The mechanisms underlying impaired diastolic function in IHD can be conventionally divided into two categories: disorders of active relaxation caused by the development of cardiosclerosis and those associated with myocardial ischemia